A Congestion Control Algorithm Based on Queuing Game for Space Information Network - Chao Guo; Haitao Xu; Guocai Jia; Zhiyong Yao (Universitas Ahmad Dahlan, 2015)
In space information network, the long delay and high link error rate are the most different characteristics from the traditional ground network. Based on the queuing game theory, a novel congestion control is proposed in this paper. It assumes that the users pay an admission fee for entering the queue, and then cost during the waiting time, at last they obtain a benefit from the node when they are serviced completely. This paper not only designs a variable admission fee in order that the proposed algorithm is more suitable for the space environment, but also considers the ending profits of the game which is described by a discount rate. The simulation result shows the proposed algorithm improve the network performance.